Method for improving alloy density based on laser printing parameters

By optimizing laser printing parameters during the SLM manufacturing process, especially determining the optimal volume energy density interval and adjusting the laser power, scanning speed and scanning spacing, the problem of Inconel 738 alloy being prone to cracks in SLM manufacturing is solved, and the density and mechanical properties of the alloy are improved.

CN119609163AInactive Publication Date: 2025-03-14SHENYANG WANWEI ZHIZAO TECH CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411789925.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-06
Publication Date
2025-03-14
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

During the selected laser melting (SLM) manufacturing process, Inconel 738 alloy is prone to cracks, and its density does not match the casting performance, and existing research focuses less on the influence of laser printing parameters on the alloy density.

Method used

By studying the influence of body energy density on alloy density, the optimal body energy density interval is determined, and the laser power, scanning speed and scanning spacing are adjusted through orthogonal experiments within this interval, and the laser printing parameters are optimized to improve the density of the alloy.

Benefits of technology

This achieves increasing the density of Inconel 738 alloy during the SLM manufacturing process, reducing the risk of cracks in the material, and further optimizing density and mechanical properties can be further optimized by adjusting the scanning speed.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119609163A_ABST
    Figure CN119609163A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of alloy additive manufacturing, and particularly relates to a method for improving alloy compactness based on laser printing parameters. A laser printing parameter interval is set, and a high-temperature alloy block is prepared through an orthogonal test within a certain body energy density interval range; a batch of printed alloy blocks are subjected to density analysis, the average density of each alloy block is obtained, and the optimal energy density interval of alloy printing is determined; in the optimal body energy density interval, the influence rule of the laser printing parameters on the density is analyzed, and the final optimal body energy density and the laser printing parameters are determined; and according to the determined optimal body energy density and laser printing parameters, alloy printing preparation is conducted. According to the method, on the premise of determining the optimal energy density, an orthogonal experiment is carried out with the laser power, the scanning speed and the scanning interval as factors, the influence of laser printing parameters on the density is determined, and printing preparation of the alloy is guided.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of alloy additive manufacturing, and specifically relates to a method for improving alloy density based on laser printing parameters. Background Art

[0002] Selective laser melting (SLM) technology has great advantages in the high-precision and rapid manufacturing of thin-walled structures with complex surfaces and cavities. In the fields of aerospace, new energy and automotive industries, some structures not only require extremely high high-temperature performance of materials, but also require complex porous thin-walled structures, such as gas turbine blades. Traditional casting and machining manufacturing methods have the problems of high processing difficulty, long processing cycle and high cost for manufacturing thin-walled multi-surface structures. At the same time, the heat exchange effect is not good due to the limitations of the processing methods. Therefore, for high-temperature components with complex surfaces and cavities, additive manufacturing (AM) has gradually become an important manufacturing method.

[0003] Inconel 738 alloy is a γ / ′-Ni3 (Al, Ti) is a precipitation-strengthened cast nickel-based high-temperature alloy with strengthening phase. It has excellent creep resistance, strength, corrosion resistance and good organizational stability in high temperature environment, and is a key material for gas turbine blades and heat sinks. However, compared with the traditional cast Inconel 738 alloy, under SLM manufacturing conditions, the extremely high temperature gradient (≥105K / cm), extremely fast cooling rate (≥0.01m / s), cyclic thermal action and the difference between high temperature phase and solidification point make Inconel 738 alloy very easy to crack during the printing process, and the comprehensive performance of the material does not match the performance of the cast state.

[0004] For the additive manufacturing process, there have been a lot of studies on the effect of laser energy density on alloy defects, but there are fewer studies on the effect of parameters such as power (P), scanning speed (v), scanning spacing (s) and layer thickness (t) that determine the laser energy density on defects. Under the condition of meeting the requirements of body energy density, the determining parameters: laser power, scanning speed, and scanning spacing should be optimized to improve the density of the alloy. Therefore, under the condition of determining the optimal energy density, it is of great significance to study the above three parameters to improve the quality of Inconel 738 in additive manufacturing. Summary of the invention

[0005] In order to solve the above technical problems, the present invention provides a method for improving the density of alloy based on laser printing parameters. Firstly, the influence of volume energy density on the density and metallurgical defects of SLM formed alloy is studied. On the premise of determining the optimal volume energy density, orthogonal experiments are carried out with laser power, scanning speed and scanning spacing as factors. The laser power and scanning speed are analyzed to determine the influence of laser power, scanning speed, etc. on the density.

[0006] The present invention is implemented by providing a method for improving alloy density based on laser printing parameters, comprising the following steps:

[0007] Step 1: Set device parameters;

[0008] Step 2: Setting the laser printing parameter range, the laser printing parameters include scanning speed, laser power and scanning spacing, and preparing the high temperature alloy block within a certain volume energy density range;

[0009] Step 3: Perform density analysis on a batch of printed alloy blocks to obtain the average density of each alloy block and determine the optimal volume energy density range for alloy printing;

[0010] Step 4: Within the optimal volume energy density range, analyze the influence of laser printing parameters on density and determine the final optimal volume energy density and laser printing parameters;

[0011] Step 5: According to the optimal volume energy density and laser printing parameters determined in step 4, the alloy is printed and prepared.

[0012] Preferably, the step 3 specifically comprises the following steps:

[0013] Step 301: After cleaning, mechanical grinding and polishing of the alloy block sample, chemical etching and cleaning are performed;

[0014] Step 302: Calculate the relative density of the alloy block sample by grayscale analysis using a binary method, take an average value of the density obtained for each alloy block sample, and obtain an average density of each alloy block sample;

[0015] Step 303: Determine the optimal volume energy density range for alloy printing according to the average density trend of the alloy block pattern.

[0016] Further preferably, in step 301, the chemical etching solution is a mixed solution of hydrochloric acid, alcohol and CuCl2, and the etching time is 1 s.

[0017] Preferably, the alloy is Inconel 738 alloy, and the method is specifically as follows:

[0018] Step 1: Set the equipment parameters: set the substrate temperature to 80°C, the chamber to be protected by Ar atmosphere, the oxygen content during the forming process to be controlled below 1000ppm, the laser scanning method to be a strip scanning strategy, and the scanning direction rotation angle between layers to be set to 67°;

[0019] Step 2: Set the laser printing parameter range. The laser printing parameters include scanning speed, laser power and scanning spacing. There are five scanning speed settings, namely 950mm / s, 1000mm / s, 1050mm / s, 1100mm / s, and 1150mm / s. There are five laser power settings, namely 260W, 270W, 280W, 290W, and 300W. There are two scanning spacing settings, namely 0.1mm and 0.11mm. The range is 50-80J / mm 3 Preparation of high temperature alloy blocks within the range of volume energy density;

[0020] Step 3: Perform density analysis on a batch of printed alloy blocks to obtain the average density of each alloy block and determine that the optimal volume energy density range for alloy printing is 60-70 J / mm 3 ;

[0021] Step 4: In the optimal volume energy density range, the influence of laser printing parameters on density is analyzed. That is, as the scanning speed increases, the density of the Inconel738 alloy block continues to decrease. In the optimal volume energy density range, the density of the Inconel738 alloy cannot be changed by changing the laser power. The final optimal volume energy density E = 66.67 J / mm 3 , laser power is 260W, scanning speed is 950mm / s, and spacing is 0.1mm;

[0022] Step 5: According to the optimal volume energy density and laser printing parameters determined in step 4, the alloy is printed and prepared.

[0023] Further preferably, the step 3 specifically comprises the following steps:

[0024] Step 301: After the Inconel 738 alloy block sample is cleaned, mechanically ground and polished, it is chemically corroded for 1 second using a mixed solution of 20 mL HCl + 20 m alcohol + 1 g CuCl2 and cleaned;

[0025] Step 302: Calculate the relative density of the alloy block sample by grayscale analysis using a binary method, take an average value of the density obtained for each alloy block sample, and obtain an average density of each alloy block sample;

[0026] Step 303: Determine the optimal volume energy density range for alloy printing according to the average density trend of the alloy block pattern.

[0027] Compared with the prior art, the advantages of the present invention are:

[0028] The present invention provides a method for improving the density of an alloy based on laser printing parameters. First, an optimal volume energy density interval is determined. Secondly, the influence of the laser printing parameters is determined by adjusting the scanning speed, laser power and scanning spacing in the optimal volume energy density interval. It is found that within the optimal volume energy density interval, there is still a variation interval of density. The scanning speed has a direct impact on the density of the sample. Within the selected scanning speed interval, the density of the sample shows a downward trend as the scanning speed increases. Therefore, the density of the additively manufactured sample can be changed by adjusting the scanning speed parameter. Finally, the optimal process parameters are determined by density and mechanical property indicators, which has important guiding significance for the additive manufacturing of alloys, especially Inconel738 alloy. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 The energy density and compactness relationship curve in the embodiment of the present invention;

[0030] Figure 2 is a curve showing the relationship between scanning speed and density in an embodiment of the present invention;

[0031] Figure 3 is a curve showing the relationship between laser power and density in an embodiment of the present invention;

[0032] Figure 4 Mechanical properties of printed samples under different printing parameters. DETAILED DESCRIPTION

[0033] The technical solutions in the embodiments of the present invention will be described clearly and completely below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments.

[0034] Example:

[0035] This embodiment takes Inconel 738 alloy as an example and provides a method for improving alloy density based on laser printing parameters, which specifically includes:

[0036] Step 1: Set the equipment parameters: set the substrate temperature to 80°C, the chamber to be protected by Ar atmosphere, the oxygen content during the forming process to be controlled below 1000ppm, the laser scanning method to be a strip scanning strategy, and the scanning direction rotation angle between layers to be set to 67°;

[0037] Step 2: Set the laser printing parameter range. The laser printing parameters include scanning speed, laser power and scanning spacing. There are five scanning speed settings, namely 950mm / s, 1000mm / s, 1050mm / s, 1100mm / s, and 1150mm / s. There are five laser power settings, namely 260W, 270W, 280W, 290W, and 300W. There are two scanning spacing settings, namely 0.1mm and 0.11mm. The range is 50-80J / mm 3 High temperature alloy blocks were prepared by orthogonal test within the range of volume energy density;

[0038] Step 3: Perform density analysis on a batch of printed alloy blocks to obtain the average density of each alloy block and determine that the optimal volume energy density range for alloy printing is 60-70 J / mm 3 ;

[0039] Step 301: After the Inconel 738 alloy block sample is cleaned, mechanically ground and polished, it is chemically corroded for 1 second using a mixed solution of 20 mL HCl + 20 m alcohol + 1 g CuCl2 and cleaned;

[0040] Step 302: Calculate the relative density of the alloy block sample by grayscale analysis using a binary method, take an average value of the density obtained for each alloy block sample, and obtain an average density of each alloy block sample;

[0041] Step 303: According to the average density trend of the alloy block pattern, determine the optimal volume energy density range for alloy printing. The relationship curve between volume energy density and density is shown in Figure 1 ;

[0042] Step 4: The law of the effect of laser power on density in the optimal volume energy density range, refer to Figure 2 In the optimal volume energy density range, the relationship between laser power and density of Inconel738 alloy obeys the volume energy density formula, that is, when other parameters are fixed, as the laser power increases, the density first increases and then decreases, obeying the reference Figure 1 It can be seen that the laser power has no additional effect on the density. When the scanning speed is 950mm / s, the density decreases with the increase of energy density. The main reason is that the selected volume energy density range is 66.67-78.94J / mm 3 , deviating from the optimal body energy density range.

[0043] In the optimal volume energy density range, the influence of laser scanning speed on density is analyzed, referring to Figure 3 ,Within the selected scanning speed range, as the scanning speed increases, the density of the Inconel738 alloy block continues to decrease.

[0044] According to the volume energy density formula, there is an inverse function relationship between volume energy density and scanning speed. The relationship between volume energy density and scanning speed was studied. It was found that when the scanning interval was 0.1 mm, under different laser powers, the density relationship of the sample showed a decreasing pattern as the laser scanning speed increased, such as Figure 3 It shows that in the optimal energy density range, the slower the laser scanning speed, the higher the relative density of the Inconel738 high-temperature alloy block. The density of the printed block can be improved by changing the laser scanning speed.

[0045] Determine the final optimal volume energy density E = 66.67 J / mm 3 , laser power is 260W, scanning speed is 950mm / s, and spacing is 0.1mm;

[0046] Step 5: According to the optimal volume energy density and laser printing parameters determined in step 4, the alloy is printed and prepared.

[0047] refer to Figure 4 , compare the mechanical properties of printed samples under different printing parameters:

[0048] Samples 1 and 2 have the same volume energy density, scanning speed of 1100 mm / s, and laser powers of 260 W and 270 W, respectively. Comparing the mechanical property curves of samples 1 and 2, it is found that the yield strength, tensile strength and elongation of samples 1 and 2 are basically the same. It can be seen that in the optimal volume energy density range, there is no definite relationship between laser power and density.

[0049] For samples No. 2 and No. 3, the laser power is 270 W and the volume energy density is roughly the same. When the scanning speeds are 1100 mm / s and 1150 mm / s respectively, the yield strength and elongation values ​​of curve No. 2 are significantly higher than those of curve No. 3. It can be seen that in the optimal volume energy density range, the faster scanning speed has an adverse effect on the mechanical properties, which is consistent with the effect of scanning speed on density mentioned above.

[0050] Samples 4 and 5 have the same scanning speed and laser power, and the best energy density is 71.0 J / mm 3 and 68.4J / mm 3 The density is 99.95% (No. 4) and 99.97% (No. 5) respectively. The mechanical properties test of the printed samples shows that the yield strength of No. 5 sample is 563.199MPa and the tensile strength is 1446.412MPa, both slightly higher than that of No. 4 sample. As for the elongation, No. 5 sample reaches 9.2%, and the plastic deformation energy is the highest. Finally, it is determined that the No. 5 sample has the best printing mechanical properties at a power of 260W, a speed of 950mm / s, and a spacing of 0.1mm.

Claims

1. A method for improving alloy density based on laser printing parameters, characterized in that: The following steps are involved: Step 1: Set device parameters; Step 2: Setting the laser printing parameter range, the laser printing parameters include scanning speed, laser power and scanning spacing, and preparing the high temperature alloy block through orthogonal test within a certain range of volume energy density; Step 3: Perform density analysis on a batch of printed alloy blocks to obtain the average density of each alloy block and determine the optimal volume energy density range for alloy printing; Step 4: Within the optimal volume energy density range, analyze the influence of laser printing parameters on density and determine the final optimal volume energy density and laser printing parameters; Step 5: According to the optimal volume energy density and laser printing parameters determined in step 4, the alloy is printed and prepared.

2. The method for improving alloy density based on laser printing parameters according to claim 1, characterized in that: The step 3 specifically comprises the following steps: Step 301: After cleaning, mechanical grinding and polishing of the alloy block sample, chemical etching and cleaning are performed; Step 302: Calculate the relative density of the alloy block sample by grayscale analysis using a binary method, take an average value of the density obtained for each alloy block sample, and obtain an average density of each alloy block sample; Step 303: Determine the optimal volume energy density range for alloy printing according to the average density trend of the alloy block pattern.

3. The method for improving alloy density based on laser printing parameters according to claim 2, characterized in that: In step 301, the chemical etching solution is a mixed solution of hydrochloric acid, alcohol and CuCl2, and the etching time is 1 second.

4. The method for improving alloy density based on laser printing parameters according to claim 1, characterized in that: The alloy is Inconel 738 alloy, and the method is specifically as follows: Step 1: Set the equipment parameters: set the substrate temperature to 80°C, the chamber to be protected by Ar atmosphere, the oxygen content during the forming process to be controlled below 1000ppm, the laser scanning method to be a strip scanning strategy, and the scanning direction rotation angle between layers to be set to 67°; Step 2: Set the laser printing parameter range. The laser printing parameters include scanning speed, laser power and scanning spacing. There are five scanning speed settings, namely 950mm / s, 1000mm / s, 1050mm / s, 1100mm / s, and 1150mm / s. There are five laser power settings, namely 260W, 270W, 280W, 290W, and 300W. There are two scanning spacing settings, namely 0.1mm and 0.11mm. The range is 50-80J / mm 3 High temperature alloy blocks were prepared by orthogonal test within the range of volume energy density; Step 3: Perform density analysis on a batch of printed alloy blocks to obtain the average density of each alloy block and determine that the optimal volume energy density range for alloy printing is 60-70 J / mm 3 ; Step 4: In the optimal volume energy density range, the influence of laser printing parameters on density is analyzed. That is, as the scanning speed increases, the density of the Inconel738 alloy block continues to decrease. In the optimal volume energy density range, the density of the Inconel738 alloy cannot be changed by changing the laser power. The final optimal volume energy density E = 66.67 J / mm 3 , laser power is 260W, scanning speed is 950mm / s, and spacing is 0.1mm; Step 5: According to the optimal volume energy density and laser printing parameters determined in step 4, the alloy is printed and prepared.

5. The method for improving alloy density based on laser printing parameters according to claim 4, characterized in that: The step 3 specifically comprises the following steps: Step 301: After the Inconel 738 alloy block sample is cleaned, mechanically ground and polished, it is chemically corroded for 1 second using a mixed solution of 20 mL HCl + 20 m alcohol + 1 g CuCl2 and cleaned; Step 302: Calculate the relative density of the alloy block sample by grayscale analysis using a binary method, take an average value of the density obtained for each alloy block sample, and obtain an average density of each alloy block sample; Step 303: Determine the optimal volume energy density range for alloy printing according to the average density trend of the alloy block pattern.

Citation Information

Patent Citations

  • Additive manufacturing method of K465 alloy powder

    CN108555296A

  • Adjusting method for low-alloy and high-strength steel laser welding process

    CN109420846A

  • Optimization method for metal 3D printing technology parameters

    CN110560685A

  • 4D printing optimization method for TiZrNb high-temperature shape memory alloy based on selective laser melting

    CN114101703A

  • Method for determining optimal printing parameters of FDM type 3D printer

    WO2023178876A1